Alcibiades II - Plato, 428? BCE-348? BCE (Salt Lake City, UT : Project Gutenberg, 1999)
"Alcibiades II" by Plato is a dialogue of disputed authenticity, likely composed in the 3rd or 2nd centuries BC. Socrates encounters the ambitious Alcibiades on his way to pray and warns him about the dangers of asking the gods for things without understanding whether they are truly good or harmful. Through questioning, Socrates explores the relationship between knowledge, ignorance, and wisdom, ultimately persuading Alcibiades to postpone his sacrifice until he can better distinguish good from evil. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Second_Alcibiades
Socrates
Release date is 1999-03-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature; Socrates, 470 BC-399 BC; Virtue -- Early works to 1800; Alcibiades